Multi-wavelength generation using a bismuth-based EDF and Brillouin effect in a linear cavity configuration - Shahi, Sharifeh; Harun, Sulaiman Wadi; Shahabuddin, Nurul Shahrizan; Shirazi, Mohammadreza Rezazadeh; Ahmad, Harith (Elsevier, 2009)
The generation of a multiple wavelength source using a bismuth-based erbium-doped fiber (Bi-EDF) in a linear cavity configuration is demonstrated. The configuration uses a pair of optical circulators at the input and output ends of the cavity to form a resonator for multi-wavelength generation in conjunction with optical couplers to inject the Brillouin pump (BP) and to tap the output at the two ends. The Brillouin erbium fiber laser (BEFL) comb with a 2.15 m of Bi-EDF has a wavelength spacing of 0.09 nm and operates in long-wavelength (L-) band region. A stable output laser comb of 50 lines is obtained at a BP of 1568.2 nm and 5 dBm and two 1480 nm pumps at 120 mW. The injected BP wavelength and power as well as the 1480 nm pump powers have a great effect on the number of lines and output power of the BEFL. This configuration is compact due to the use of the significantly shorter Bi-EDF as the linear gain medium, and can be made more compact by replacing the single-mode fiber with highly non-linear fibers such as holey fibers.